Poor and wise: The New Granada Enlightenment in Search of the "Honest Way of Living" 1791-1797 - Silva Prada, Natalia (1996)
The emergence and spread of an "enlightened common sense" in the second half of the eighteenth century gave rise, among other things, to the reconceptualization of Christian charity. The intimate relationship of this theological virtue with almsgiving, as a means to exercise it, was questioned in the reflections of the enlightened people of the New Kingdom of Granada who intended to build a new society under the principles of utility, the value of work, happiness and the prosperity of the State and the individual. Regarding the exercise of charity, the difference between imprudent charity and discreet charity began to be discerned. The new awareness that arose around this problem was closely linked to the need they saw to "banish" the poor from the streets, an action that could be possible through a change in the way of conceiving charity.